Effects of furcation involvement on molar survival in periodontally treated patients - Nurul Ain Mohamed Yusof; Mohd Azri Mohd Suan; Rusmizan Yahaya (Universidad de Concepción., 2024)
Objective: This study aims to analyze the survival time of molar tooth according to furcation involvement (FI) classification among periodontally treated patients under a supportive periodontal care program. Materials and Methods: A retrospective study was con-ducted among 77 periodontitis patients with 240 molars who had undergone periodontal therapy that were followed up with supportive periodontal therapy (SPT) for at least five years. Periodontitis patients' data were retrieved from the periodontic clinical record. The clinical parameters of all involved molars and treatment modality were recorded at baseline and SPT. Results: A total of 69 (28.8%) molars were extracted during active periodontal therapy, while 17 (7.1%) were lost during SPT. The 5-year survival rate of molars was 83.5% (95% confidence interval [CI], 76.9-88.4) for FI=0 (n=141), 81.0% (95% CI, 56.9-92.4) for FI=I (n=18), 50.0% (95% CI, 33.8-64.2) for FI=II (n=21), and 25.0% (95% CI, 6.9-48.8) for FI=III (n=4). Additionally, the 10-year survival rate for molars with FI = III was 12.5% (95% CI, 1.0-39.2), which was lower than that of molars with FI = 0 (77.1%; 95% CI, 69.7-83.0). Conclusions: The presence of a high degree of FI classifica-tion, especially Class III, is associated with a lower survival rate of molars among periodontally treated patients. Retention of molars is possible on a long-term basis through a maintenance program of periodontal therapy.